ANALISIS KESULITAN SISWA DALAM MEMAHAMI SOAL CERITA MATEMATIKA DITINJAU DALAM ASPEK BAHASA: ANALISIS KESULITAN SISWA DALAM MEMAHAMI SOAL CERITA MATEMATIKA DITINJAU DALAM ASPEK BAHASA - Panjaitan, Chesia Aprina; Sihombing, Kesia; Anggelina, Maya; Simanullang, Asria Ronauli; Febriana, Ika (STKIP Subang, 2026)
Students’ ability to understand mathematical word problems remains a complex issue, particularly when they are faced with language usage embedded in the problems. This study aims to analyze students’ difficulties in understanding mathematical word problems from a language perspective. This research employs a qualitative approach with a descriptive method. The subjects of this study were eleventh-grade students of SMA Negeri 6 Medan. Data were collected through a test consisting of five mathematical word problems and documentation of students’ work. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that students still experience various difficulties in understanding mathematical word problems related to language aspects, including understanding mathematical vocabulary, sentence structure, interpretation of problem meaning, ability to connect information, and the ability to transform language into mathematical models.